Constructing three-dimensional Li-transport channels within the Fe3O4@SiO2@RGO composite to improve its electrochemical performance in Li-ion batteries. Issue 11 (1st August 2020) - Hu, Zhongliang; Cui, Houquan; Li, Jingying; Lei, Gangtie; Li, Zhaohui
Abstract: Magnetite Fe3 O4 particles are usually pulverized when used as the anode material for Li-ion batteries and thus the solid electrolyte interface film grows on the surface progressively, leading to inferior cycling performance and poor rate capability. To solve these issues, core-shell Fe3 O4 @SiO2 particles are wrapped by reduced graphene oxide (RGO), and meso-/micro-pores are produced not only in the SiO2 layers but also in the RGO nanosheets by chemical etching, forming three-dimensional (3D) continuous channels for Li + transportation. Benefiting from this unique structure, the as-prepared Fe3 O4 @mSiO2 @RGO composite can deliver a capacity of 1630 mA h g −1 at 0.1 A g −1 over the potential range of 0.01–3.00 V (vs. Li + /Li) in the first discharge along with an initial coulombic efficiency of 86%, and can retain the capacity of 514 mA h g −1 at 5 A g −1 after 1000 cycles, exhibiting an outstanding rate capability and a long-term span life. The results indicate that pseudocapacitive behavior enables this composite to charge/discharge fast while the porous SiO2 shell and RGO nanosheets effectively accommodate the volume change of the Fe3 O4 particles during cycling. Our findings provide a feasible strategy for improving the electrochemical properties of the Fe3 O4 anode in Li-ion batteries.